A Study on the Performance of State Road Transport Undertakings - Planning Commission (Planning Commission, 1986)
The study evaluates the performance of State Road Transport Undertakings (SRTUs) in India between 1980 and 1986, focusing on fleet utilization, financial management, staff productivity, and operational efficiency. Despite improvements in bus productivity and revenue generation, persistent challenges such as overaged fleets, rising operational costs, and uneven fare structures affected overall financial sustainability. The report recommends strategic reforms including rationalized fare policies, better resource allocation, enhanced monitoring of capital investments, and adoption of cost-efficient operational practices to strengthen SRTU performance and ensure sustainable public transport services.
Planning Commission Transport Division May, 1986
Planning Commission Transport Division May, 1986
Keywords: State Road Transport Undertakings; SRTUs; Fleet Management; Operational Efficiency; Financial Performance; Fare Structure; Overaged Fleet; Revenue Management; Staff Productivity; Cost Control; Resource Allocation; Public Transport